Analysis of Carrying Capacity and Capacity of Availability of Clean Water in Maros - Ahmad Fausy; Fuad Aziz; Emil Salim Rasyidi (Fakultas Teknik Universitas Bosowa, 2022)
When the carrying capacity and capacity of the environment in an area has been exceeded, the negative impact on the environment will appear so that it is no longer able to support and support various needs for life for humans living in that area. One important aspect that is taken into account in the carrying capacity and capacity is the availability of clean water. So the purpose of this study is to determine the carrying capacity and capacity of the availability of clean water in Maros Regency and to find out how the strategy for fulfilling water availability in Maros Regency is. This research is also expected to be a reference material for the government as a strategy in meeting the water needs of the community in Maros Regency. This study uses a quantitative approach method. When the formula used to calculate the carrying capacity of the air is the runoff coefficient method of the Minister of Environment Regulation No. 17 of 2009 by comparing water availability and water demand. The results of this study indicate that the carrying capacity of water in Maros Regency in general in 2021 will experience a surplus with an area of ​​143,331.69 Ha, a deficit of 9,154.76 Ha, and a balanced area of ​​498.43 Ha.